Development Of MAC-Based Smarthome Access Rights Authentication (Media Access Control) Address - Maulida, Sahraeni; Zain, Satria Gunawan; Yahya, Muhammad (PT. Lontara Digitech Indonesia, 2023)
This study seeks to understand the purpose of using the ESP32 module as a control center in the electronic equipment control system on Smarthome and to ascertain the outcomes of the application design by utilizing Mac Address as Authentication Access rights to control electronic equipment. A methods for gathering data utilized literary analysis. In this study, access rights authentication was conducted on the software, and two hardware test, manual mode testing and automatic mode testing, were applied. Software testing was done by registering the user and Mac address of the device by the admin, then the data is stored in the firebase. In software testing, three smartphones were used whose MAC addresses were registered by the administrator. Each registered device was tried to log in ten times, and the success rate was 100%. In contrast, three devices' MAC addresses were not registered, and they were unable to log in ten times, with a 100% failure rate. Hardware testing is carried out by manual testing mode, in manual model testing the input from the controller application is in accordance with the prototype output, while automatic mode testing is carried out based on conditions at room temperature, namely in room conditions > 30 then the fan turns on automatically, the temperature room <30 the lights turn on automatically, so the automatic mode test has been matched to the output of the prototype. Based on the results of the study, a control system was produced with a MAC Address as an id and a user to login to an application called “Controller” which can be used to control electronic equipment in the house.